2019
DOI: 10.1111/jop.12814
|View full text |Cite
|
Sign up to set email alerts
|

Chronic recurrent osteomyelitis: A surgeon's enigma

Abstract: Background Chronic recurrent forms of osteomyelitis of the mandible with their morbid clinical course have long been considered a challenge to maxillofacial surgeons in terms of both diagnosis and treatment. Various classifications and treatments have been established through the ages to define and manage the inflammatory symptoms occurring in adults and children. This paper discusses two such entities occurring in an adult and a child, highlighting the diagnostic and treatment challenges of recurrent osteomye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…However, the destruction of this kind of blood vessels will in turn promote the reconstruction of endosteal blood vessels and facilitate the formation of new bone [ 12 – 14 ]. Studies have reported that Staphylococcus aureus infection is the most common cause of sclerosing osteomyelitis [ 15 ]. Staphylococcus aureus will enter osteoblasts for long-term survival after infecting bone tissue, and form bacterial biofilm on the surface of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the destruction of this kind of blood vessels will in turn promote the reconstruction of endosteal blood vessels and facilitate the formation of new bone [ 12 – 14 ]. Studies have reported that Staphylococcus aureus infection is the most common cause of sclerosing osteomyelitis [ 15 ]. Staphylococcus aureus will enter osteoblasts for long-term survival after infecting bone tissue, and form bacterial biofilm on the surface of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomyelitis of the jaws is an extensive group of inflammatory conditions that affect the medullary portion of the bones with distinct clinical, radiographic, and etiological aspects 1 . Due to improvements in the population's oral health, together with pharmacological advances and early diagnosis, the number of cases of osteomyelitis of the jaws has been reduced over the years 2 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the lack of a standardized evidence‐based approach to antibiotic treatment of bone infection often leads to controversy regarding antibiotic selection, route of administration (intravenous versus oral), and duration of therapy 11 . This may account for inadequate patient outcomes and high recurrence rate 12 …”
Section: Introductionmentioning
confidence: 99%